Levistilide A Ameliorates NLRP3 Expression Involving the Syk-p38/JNK Pathway and Peripheral Obliterans in Rats. (12th August 2018) - Guo, Huining; Sun, Li; Ling, Shuang; Xu, Jin-Wen
Abstract : Background . Inflammation is one of the most important pathogeneses of thromboangiitis obliterans (TAO). The NLRP3 inflammasome plays a vital role in the body's immune response and disease development. It can be activated by numerous types of pathogens or danger signals. As the core of the inflammatory response, the NLRP3 inflammasome may provide a new target for the treatment of various inflammatory diseases. Levistilide A (LA) is a phthalide dimer isolated from umbelliferous plants. Its pharmacological effect is largely unknown. This study revealed the effects of LA on endothelial cell activation, NLRP3, IL-1 β, TNF- α, IL-32, and CCL-2, VCAM-1, MCP-1, and the spleen tyrosine kinase (Syk)--p38/JNK signaling axis and its effect on vasculitis in rats. Results . LA inhibited endothelial activation and the expression of IL-1 β, TNF- α, IL-32, CCL-2, VCAM-1, and MCP-1. LA directly obstructed Syk phosphorylation and activity in a dose-dependent manner, inhibited the activity of p38 and JNK, and reduced the expression of NLRP3 in human umbilical vein endothelial cells and vascular tissue of rats with vasculitis. Conclusion . LA suppressed NLRP3 gene expression by blocking the Syk--p38/JNK pathway and reduced damage to the rats' limbs in the thromboangiitis obliterans model.